Linkage Disequilibrium with Linkage Analysis of Multiline Crosses Reveals Different Multiallelic QTL for Hybrid Performance in the Flint and Dent Heterotic Groups of Maize. Issue 4 (29th September 2014) - Giraud, Héloïse; Lehermeier, Christina; Bauer, Eva; Falque, Matthieu; Segura, Vincent; Bauland, Cyril; Camisan, Christian; Campo, Laura; Meyer, Nina; Ranc, Nicolas; Schipprack, Wolfgang; Flament, Pascal; et al.
Abstract: Multiparental designs combined with dense genotyping of parents have been proposed as a way to increase the diversity and resolution of quantitative trait loci (QTL) mapping studies, using methods combining linkage disequilibrium information with linkage analysis (LDLA). Two new nested association mapping designs adapted to European conditions were derived from the complementary dent and flint heterotic groups of maize ( Zea mays L.). Ten biparental dent families ( N = 841) and 11 biparental flint families ( N = 811) were genotyped with 56, 110 single nucleotide polymorphism markers and evaluated as test crosses with the central line of the reciprocal design for biomass yield, plant height, and precocity. Alleles at candidate QTL were defined as (i) parental alleles, (ii) haplotypic identity by descent, and (iii) single-marker groupings. Between five and 16 QTL were detected depending on the model, trait, and genetic group considered. In the flint design, a major QTL ( R 2 = 27%) with pleiotropic effects was detected on chromosome 10, whereas other QTL displayed milder effects ( R 2 < 10%). On average, the LDLA models detected more QTL but generally explained lower percentages of variance, consistent with the fact that most QTL display complex allelic series. Only 15% of the QTL were common to the two designs. A joint analysis of the two designs detected between 15 and 21 QTL for the five traits. Of these, between 27 for silking date and 41% for tasseling date were significant in both groups. Favorable allelic effects detected in both groups open perspectives for improving biomass production.